Implementasi Program SIM Online Untuk Meningkatkan Pelayanan Publik Dalam Rangka Terciptanya Pelayanan Publik Yang Modern Dan Transparan - Sudjarno, Robbi January (Indonesian Journal of Police Studies, 2020)
This research is motivated by many inputs and criticisms related to making conventional SIM that require a long time and the process is fairly complicated. In addition, there are many brokers or illegal services offer making a SIM that requires the applicants to pay a considerable amount of money as a reward. One way to overcome this problem is that the National Traffic Police Corps has made an innovation by creating an Online SIM program which does not require a long time to make a SIM and free practice of brokers, which has been implemented by all police station in Indonesia, one of which is the Bogor Police Station. On the issues discussed using management theory in the elaboration of P.O.A.C there is a fact that the program has a good planning, organization and implementation that has received a positive response from both the police and community leaders and supervision that has standards set by the leadership. And advocacy theory analyzes that the program is a policy change in making SIMs for the creation of modern and transparent public services. In the research that the author investigated there are several sources that are important write the basis of this study, namely previous research and some references that the author took from the book. And in this study the authors conducted research at Bogor Police Station. The results of the study found that the implementation of the Online SIM program in Bogor Police after being analyzed using management theory was assessed as an effective program and if analyzed using advocacy theory, the Online SIM program was one of the ways to make a change from the problems that occurred before. The program is an innovation resulting from current technological developments, so the Traffic Police Corps utilizes it to overcome the problems that occurred before, with this program is an effort to create a modern and transparent public service, and in the program there are good inhibiting factors as well as supporters for the implementation of the Online SIM program.